Long-term follow-up of a female with congenital adrenal hyperplasia due to P450-oxidoreductase deficiency - Beatriz D. S. F. Bonamichi; Stella L. M. Santiago; Débora R. Bertola; Chong A. Kim; Nivaldo Alonso; Berenice B. Mendonca; Tania A. S. S. Bachega; Larissa G. Gomes (Archives of Endocrinology and Metabolism, 2016)
SUMMARY P450 oxidoreductase deficiency (PORD) is a variant of congenital adrenal hyperplasia that is caused by POR gene mutations. The POR gene encodes a flavor protein that transfers electrons from nicotinamide adenine dinucleotide phosphate (NADPH) to all microsomal cytochrome P450 type II (including 21-hydroxylase, 17α-hydroxylase 17,20 lyase and aromatase), which is fundamental for their enzymatic activity. POR mutations cause variable impairments in steroidogenic enzyme activities that result in wide phenotypic variability ranging from 46,XX or 46,XY disorders of sexual differentiation, glucocorticoid deficiency, with or without skeletal malformations similar to Antley-Bixler syndrome to asymptomatic newborns diagnosed during neonatal screening test. Little is known about the PORD long-term evolution. We described a 46,XX patient with mild atypical genitalia associated with severe bone malformation, who was diagnosed after 13 years due to sexual infantilism. She developed large ovarian cysts and late onset adrenal insufficiency during follow-up, both of each regressed after hormone replacement therapies. We also described a late surgical approach for the correction of facial hypoplasia in a POR patient.